FACTORS ASSOCIATED WITH DISEASE DURATION AND LESION PERSISTENCE IN PATIENTS WITH CHRONIC URTICARIA AT BINH THUAN GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to identify factors associated with disease duration and lesion persistence in patients with chronic urticaria.Subject and methods: An analytical cross-sectional study was conducted on 52 patients with chronic urticaria who presented to Binh Thuan General Hospital from August 2015 to June 2016. The investigated factors included infection with Helicobacter pylori, hepatitis B virus, and several parasites. Disease duration and lesion persistence were recorded and their associations were analyzed using Chi-square, Fisher exact and t-tests with a significance level of p < 0,05.Results: No significant differences were found in disease duration or lesion persistence between patients with and without H.pylori infection (p > 0,05). Lesion persistence also did not differ significantly between patients with and without hepatitis B virus infection, whereas disease duration differed between these two groups. Patients with parasitic infections had a higher proportion of prolonged lesion persistence (≥ 4 hours) and a significantly longer mean disease duration compared with those without parasitic infection (p < 0,05).Conclusion: Parasitic infection was significantly associated with both lesion persistence and disease duration in patients with chronic urticaria. In addition, disease duration differed significantly between patients with and without hepatitis B virus infection. In contrast, no association was observed between H.pylori infection and either disease duration or lesion persistence. These findings suggest that screening for infectious factors, particularly parasitic infections, may be useful in the comprehensive evaluation of patients with chronic urticaria. Further studies with larger sample sizes are needed to clarify the role of these factors.
Keywords: Chronic urticaria, Helicobacter pylori, parasitic infection, hepatitis B virus.